2016
DOI: 10.1016/j.jglr.2016.03.002
|View full text |Cite
|
Sign up to set email alerts
|

Urea in Lake Erie: Organic nutrient sources as potentially important drivers of phytoplankton biomass

Abstract: Significant evidence shows that nitrogen (N) supply may influence microbial community structure and, in some cases, the rate of primary productivity in fresh waters. To date, however, most focus has been on dissolved inorganic N (i.e., ammonia and nitrate), or dinitrogen gas. Far less is known about the effects of dissolved organic N such as urea on plankton activity, although this compound is both produced by in-lake processes and is a significant component of external loading. We evaluated the urea distribut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
43
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 56 publications
(50 citation statements)
references
References 49 publications
6
43
1
Order By: Relevance
“…levels in the Manokin watershed ranged from 0.015 to 0.221 mg N/L, which was consistent with published studies documenting urea-N concentrations of <0.001-1.441 mg N/L in freshwater and brackish environments (Table 3). Even though urea-N is widely recognized for its role in eutrophying freshwaters (Finlay et al 2010;Belisle et al 2016) and coastal zones , it is rarely included in most water quality analyses (Paerl et al 2016). Peak urea-N values that we observed in the Manokin Basin (0.221 mg N/L) were generally sevenfold lower than those reported by Glibert et al (2005) in nearby waters (1.441 mg N/L).…”
Section: Urea-n Concentrations In Nontidal and Tidal Watershedscontrasting
confidence: 70%
See 1 more Smart Citation
“…levels in the Manokin watershed ranged from 0.015 to 0.221 mg N/L, which was consistent with published studies documenting urea-N concentrations of <0.001-1.441 mg N/L in freshwater and brackish environments (Table 3). Even though urea-N is widely recognized for its role in eutrophying freshwaters (Finlay et al 2010;Belisle et al 2016) and coastal zones , it is rarely included in most water quality analyses (Paerl et al 2016). Peak urea-N values that we observed in the Manokin Basin (0.221 mg N/L) were generally sevenfold lower than those reported by Glibert et al (2005) in nearby waters (1.441 mg N/L).…”
Section: Urea-n Concentrations In Nontidal and Tidal Watershedscontrasting
confidence: 70%
“…Nevertheless, 14% of baseflow urea-N concentrations exceeded the 0.06 mg N/L threshold that could potentially trigger harmful algal blooms (Glibert et al 2004). Even though urea-N is widely recognized for its role in eutrophying freshwaters (Finlay et al 2010;Belisle et al 2016) and coastal zones , it is rarely included in most water quality analyses (Paerl et al 2016). Results from the Manokin River watershed clearly demonstrate that urea-N is a ubiquitous form of DON in nontidal streams and tidal rivers, and therefore highlight the importance Notes: GW, groundwater.…”
Section: Urea-n Concentrations In Nontidal and Tidal Watershedsmentioning
confidence: 99%
“…In addition, Donald et al (2011) explored that the NH 4 -N and urea favored non-heterocystous cyanobacteria, and microcystin production was increased by up to 13-fold after N added. Belisle et al (2016) also evaluated the urea distribution and the urease activity in Lake Erie and confirmed that organic nitrogen source was an important driver of cyanobacterial blooms and toxin production.…”
Section: Introductionmentioning
confidence: 78%
“…Historically, N in fertilisers were based on nitrate (NO3) and ammonium (NH4+), but in recent years, there has been a shift towards urea (CO(NH 2 ) 2 )‐based fertilisers (Belisle et al., ; Glibert et al., ). Although NO3/NH4+‐based fertilisers are still used today in some regions, urea‐based fertilisers are now the primary N source applied to agricultural landscapes (Glibert et al., ).…”
Section: Introductionmentioning
confidence: 99%
“…As organisms strategically select pathways that offer the greatest energetic return or least amount of manipulation, it is possible that urea could be a more energetically favourable N source compared to NH þ 4 . Historically, N in fertilisers were based on nitrate (NO À 3 ) and ammonium (NH þ 4 ), but in recent years, there has been a shift towards urea (CO(NH 2 ) 2 )-based fertilisers (Belisle et al, 2015;Glibert et al, 2006). Although NO À 3 /NH þ 4 -based fertilisers are still used today in some regions, urea-based fertilisers are now the primary N source applied to agricultural landscapes (Glibert et al, 2014).…”
Section: Introductionmentioning
confidence: 99%